A Two-Step Synthesis of Selected 1,2,3,4-Tetrahydroquinoxaline Derivatives from N-Aryl-2-nitrosoanilines and Arylidenecyanoacetic Esters - Królikiewicz, Magdalena; Błaziak, Kacper; Danikiewicz, Witold; Wróbel, Zbigniew (Synlett, 2013)
Reaction of N-aryl-2-nitrosoanilines with alkyl arylidenecyanoacetates in the presence of Et3N in MeCN leads to substituted 1,2,3,4-tetrahydroquinoxaline derivatives in reasonable yields. The reaction comprises nucleophilic addition of the nitrosoaniline to the Michael acceptor followed by cyclization involving the nitroso group. Since the reactive nitrogen groups in N-aryl-2-nitrosoanilines are of opposite character the reaction is regioselective and additionally it was found to be diastereoselective.
Keywords: Michael addition; ring closure; condensation; heterocycles; reduction